Electronic response of a Mott insulator at a current-induced insulator-to-metal transition - Suen, C. T.; Marković, I.; Zonno, M.; Heinsdorf, N.; Zhdanovich, S.; Jo, N. H.; Schmid, M.; Hansmann, Philipp; Puphal, P.; Fürsich, K.; Smit, S.; Au-Yeung, C.; et al. (Nature Physics, 2024)
The Mott insulator Ca2RuO4 exhibits an insulator-to-metal transition induced by d.c. current. Despite the thorough examination of the structural changes associated with this transition, a comprehensive knowledge of the response of electronic degrees of freedom is still lacking. Here we demonstrate current-induced modifications of the electronic states of Ca2RuO4. Angle-resolved photoemission spectroscopy in conjunction with four-probe electrical transport (transport-ARPES) measurements reveal a clear reduction of the Mott gap and a modification in the dispersion of the Ru bands. Based on a free-energy analysis, we show that the current-induced phase is electronically distinct from the high-temperature zero-current metallic phase. Our results highlight strong interplay of lattice- and orbital-dependent electronic responses in the current-driven insulator-to-metal transition.
CRIS-Team Scopus Importer:2024-10-18